Mindful Parenting and Emotional Regulation in Early Childhood: A Systematic Literature Review - Citra Dewi (Pt. Anagata Sembagi Education, 2026)
Mindful parenting is increasingly being researched as a protective factor for the development of children's emotion regulation during early childhood, a critical period for establishing the neurobiological and psychosocial foundations of selfcontrol. This article aims to synthesize current empirical evidence on the relationship between mindful parenting and early childhood emotion regulation through a systematic literature review approach following the PRISMA 2020 guidelines. A search of Scopus, Web of Science, PubMed, ProQuest, and Google Scholar databases for articles published in the past five years yielded twentyfive articles that met the inclusion criteria after identification, screening, and eligibility assessment. The synthesis results indicate that mindful parenting contributes to children's emotion regulation through three main pathways: increased parental sensitivity and responsiveness, decreased parenting stress and depressive symptoms, and strengthened parentchild relationship quality. Contextual factors such as paternal involvement, household turmoil, and socioeconomic status also moderate these relationships. The novelty of this article lies in the integrated mapping of mediationmoderation mechanisms across Western and Asian cultures, which has not been widely integrated in previous reviews. These findings provide important implications for the development of mindfulnessbased intervention programs to support family mental health and early childhood emotional development.